Implementasi Algoritma Left Corner Parsing Dalam Pencarian Surat Pada Arsip Surat Masuk dan Surat Keluar - Pratiwi, Indah (Bulletin of Data Science, 2022)
Archives are notes written, printed or typed in the form of letters, numbers or pictures, which have certain meanings and purposes as communication and information materials recorded on form cards, film paper, photocopy paper and others. Letters are one of the important tools in an organization because a lot of important information is contained in it, so proper management is needed so that there are no errors such as scattered or damaged letters that can cause losses to the agency concerned. It takes a long time to find a letter, especially in large numbers. For this reason, a complete mail administration system is needed with a more structured mail search process in order to assist the administration in managing the more efficient archiving of incoming and outgoing mail and maintaining physical mail can be maintained. And to facilitate the search for letters in the archive of incoming and outgoing mail, a search application for the mail archive is designed using the Left Corner Parsing algorithm. The Left Corner Parsing Algorithm is one of the algorithms that can be used to search by matching keywords with text. From the experiments carried out, the Left Corner Parsing algorithm can recognize grammatical patterns and recognize meaning very well.